2014
DOI: 10.5539/ijbm.v9n12p239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hofstede’s Cultural Dimensions on Subordinate’s Perception of Abusive Supervision

Abstract: This study is designed to explore and identify the impact of Hofstede's cultural dimensions on employees' perception of their supervisory abuse in a cross-cultural context e.g. Australia and Pakistan. This study is a conceptual and a literature review in nature, since the aim was to highlight and identify with the help of prior research the impact of Hofstede's cultural dimensions on the employees' perception of their supervisory abuse in a western and eastern cultural context e.g. Australia and Pakistan. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the degree of power distance orientation in a given culture impacts perception of abusive supervision. For example, abusive supervision is perceived to be less acceptable in low power contexts, such as Australia (Khan, 2014) and the USA (Vogel et al, 2015), compared to high power distance contexts, such as Pakistan (Khan, 2014), Singapore and Taiwan (Vogel et al, 2015), and China (Pan & Lin, 2017). Similarly, people with high power distance orientation at individual level are expected to respect authority and be less likely to question it (Earley & Erez, 1997;Maznevski et al, 2002).…”
Section: Stage 2: Interpretation Of the Situationmentioning
confidence: 99%
“…Previous studies have shown that the degree of power distance orientation in a given culture impacts perception of abusive supervision. For example, abusive supervision is perceived to be less acceptable in low power contexts, such as Australia (Khan, 2014) and the USA (Vogel et al, 2015), compared to high power distance contexts, such as Pakistan (Khan, 2014), Singapore and Taiwan (Vogel et al, 2015), and China (Pan & Lin, 2017). Similarly, people with high power distance orientation at individual level are expected to respect authority and be less likely to question it (Earley & Erez, 1997;Maznevski et al, 2002).…”
Section: Stage 2: Interpretation Of the Situationmentioning
confidence: 99%
“…The findings of this research are consistent with the perspective of De Clercq et al (2020) that holds abusive leadership responsible for employees’ deviant behavior. Similarly, cultural context (e.g., high power distance) shapes the employees’ perception regarding the abuse of their leaders (S. N. Khan, 2014), confirming that the submissive behavior of employees allows mistreatment from abusive leaders.…”
Section: Discussionmentioning
confidence: 80%
“…In comparison to western nations, where the majority of the research work on "abusive supervision" is centered, Pakistan belongs to a high power distance culture [22]. Power distance is the acceptance of employees to the unfair distribution of the organizational resources [23].…”
Section: Methodsmentioning
confidence: 99%
“…Second, the data collection from education systems existing in developing countries, i.e., universities in AJK working under the Higher Education Commission (HEC), enhances the study's uniqueness. In comparison to western nations, where the majority of research work on "abusive supervision" is centered, Pakistan belongs to a high power distance culture [22]. Power distance is the acceptance of employees to the unfair distribution of organizational resources [23].…”
Section: Introductionmentioning
confidence: 99%